(Dis)Connectivity in catchment sediment cascades: a fresh look at the sediment delivery problem. Issue 1 (23rd April 2012) - Fryirs, Kirstie
ABSTRACT The concept of the sediment delivery problem was introduced into the literature in 1983 by Des Walling. This concept describes how only a fraction of sediment eroded within a catchment will reach the basin outlet and be represented as sediment yield, and that sediment storage mechanisms operating within a catchment explain this discrepancy. Since this paper was published, geomorphologists have been examining in great detail the fate of sediment eroded from the landsurface, and the pathways and timeframes of sediment transport and storage in catchments. However, to fully understand the internal dynamics of sediment flux requires a 'fresh look at the sediment delivery problem'. A framework is required that can incorporate the various processes involved in sediment movement from source areas through a basin to its outlet, and can take account of the spatial distribution of, and timeframes over which, these processes operate. This paper presents a conceptual framework for analysis of catchment (dis)connectivity that incorporates both spatial and temporal variability in the operation of the sediment cascade. This approach examines where blockages occur to disrupt these longitudinal, lateral and vertical linkages in catchments. Depending on the position of blockages (termed buffers, barriers and blankets), and their sediment residence time, various parts of a catchment may be actively contributing sediment to the sediment cascade and be switched on, or inactive and switched off. This paper discusses how such a framework can be used to model response times to disturbance and explain the manifestation of geomorphic change in catchments. The paper then highlights challenges geomorphologists face in applying such a framework to understand the internal dynamics of the catchment sediment cascades, and forecast how environmental change might affect the operation of sediment fluxes into the future. Copyright © 2012 John Wiley & Sons, Ltd.